Australian validation of the Cancer of the Prostate Risk Assessment Post‐Surgical score to predict biochemical recurrence after radical prostatectomy. Issue 3 (4th May 2017) - Beckmann, Kerri; O'Callaghan, Michael; Vincent, Andrew; Roder, David; Millar, Jeremy; Evans, Sue; McNeil, John; Moretti, Kim
Abstract : Background: The Cancer of the Prostate Risk Assessment Post‐Surgical (CAPRA‐S) score is a simple post‐operative risk assessment tool predicting disease recurrence after radical prostatectomy, which is easily calculated using available clinical data. To be widely useful, risk tools require multiple external validations. We aimed to validate the CAPRA‐S score in an Australian multi‐institutional population, including private and public settings and reflecting community practice. Methods: The study population were all men on the South Australian Prostate Cancer Clinical Outcomes Collaborative Database with localized prostate cancer diagnosed during 1998–2013, who underwent radical prostatectomy without adjuvant therapy ( n = 1664). Predictive performance was assessed via Kaplan–Meier and Cox proportional regression analyses, Harrell's Concordance index, calibration plots and decision curve analysis. Results: Biochemical recurrence occurred in 342 (21%) cases. Five‐year recurrence‐free probabilities for CAPRA‐S scores indicating low (0–2), intermediate (3–5) and high risk were 95, 79 and 46%, respectively. The hazard ratio for CAPRA‐S score increments was 1.56 (95% confidence interval 1.49–1.64). The Concordance index for 5‐year recurrence‐free survival was 0.77. The calibration plot showed good correlation between predicted and observed recurrence‐free survival across scores. Limitations include the retrospective nature and small numbers with higher CAPRA‐S scores. Conclusions: The CAPRA‐S score is an accurate predictor of recurrence after radical prostatectomy in our cohort, supporting its utility in the Australian setting. This simple tool can assist in post‐surgical selection of patients who would benefit from adjuvant therapy while avoiding morbidity among those less likely to benefit.